PERAN WARGA PEDULI AIDS CAHAYA CARE TUREN DALAM MENINGKATKAN KUALITAS HIDUP ODHA - Tri Nurhudi Sasono (Jurnal Kesehatan Mesencephalon, 2017)
Abstract : Indicator of the health welfare through Sustanable Development Goals (SDGs) is to reduce the incidence of HIV-AIDS, decrease the rate of the epidemic and maintain the quality of life of people living with HIV-AIDS (PLWHA). Trend cases of HIV-AIDS is the most recent spread among people, especially housewives. In Malang until 2015 found 278 Housewife of 409 cases of AIDS. The prevalence of HIV-AIDS in Malang Regency is ranked second after Surabaya city in East Java. For the importance of public participation and citizen care AIDS Cahaya Care Turen take responsibility for the condition. Determination Rule Goverment number 2 2015 year on the Participation of the community response to HIV-AIDS in Malang as a legal rule. Concerned Citizens activities AIDS (WPA). WPA Cahaya Care Turen is increases HIV risk and quality of life PLWHA. The purpose of this study was to determine the role of Citizens AIDS Cahaya Care Quality of Care Turen against people living with HIV in Puskesmas Turen Malang. The study design using a quasi-experimental, with purposive sampling using a sampling technique. Total number of research subjects 23. Based on test results obtained with the Wilcoxon p value <0.005, which means that there is a significant difference before and after PLWHA joining participated in the WPA Cahaya Care Turen. The conclusion of this study is WPA activities involving people living with HIV and at risk groups can optimize compliance with antiretroviral drugs that have an impact on improving the quality of life of PLHIV. Suggestions in this research is done WPA Program activities are structured and ongoing cross-sector in order to improve the quality of life and empower PLWHA.Keywords : WPA Cahaya Care Turen, Quality of life, PLWHA Abstrak : Salah satu indikator kesejahteraan kesehatan melalui Sustanable Development Goals (SDGs) adalah menekan angka kejadian HIV-AIDS, menurunkan laju epidemik dan mempertahankan kualitas hidup Orang dengan HIV-AIDS (ODHA). Trend kasus HIV-AIDS terkini terbanyak adalah menjangkit dikalangan masyarakat khususnya pada ibu rumah tangga. Kabupaten Malang sampai dengan tahun 2015 ditemukan 278 Ibu Rumah Tangga dari 409 kasus AIDS. Prevalensi HIV-AIDS di Kabupaten Malang ini merupakan peringkat kedua di Jawa Timur setelah Kota Surabaya. Untuk itu pentingnya peran serta masyarakat dan warga peduli AIDS Cahaya Care Turen ikut bertanggung jawab terhadap kondisi tersebut. Penetapan Peraturan Bupati Malang no.2 th.2015 tentang Peran serta masyarakat penanggulangan HIV-AIDS di Kabupaten Malang diharapkan dapat mengurangi risiko penularan HIV dan meningkatkan kualitas hidup ODHA. Tujuan dari penelitian ini adalah untuk mengetahui Peran Warga Peduli AIDS Cahaya Care Turen terhadap Kualitas ODHA Di Wilayah Kerja Puskesmas Turen Kabupaten Malang. Desain penelitian menggunakan quasi eksperimen, dengan teknik sampling menggunakan purposive sampling. Jumlah subyek penelitian sejumlah 23. Berdasarkan hasil uji dengan Wilcoxon didapatkan nilai p value < 0.005 yang berarti bahwa terdapat perbedaan bermakna sebelum dan sesudah ODHA bergabung mengikuti kegiatan WPA Cahaya Care Turen. Kesimpulan dalam penelitian ini adalah kegiatan WPA dengan melibatkan ODHA dan kelompok beresiko dapat mengoptimalkan kepatuhan obat ART sehingga berdampak terhadap peningkatan kualitas hidup ODHA. Saran dalam penelitian ini adalah dilakukannya Program kegiatan WPA yang terstruktur dan berkesinambungan lintas sektor guna meningkatkan kualitas hidup dan memberdayakan ODHA.     Kata kunci : WPA Cahaya Care Turen, kualitas hidup, ODHA